Membangun Kecerdasan Spiritual Anak Perspektif Surat Luqman - Yuliatun, Etik (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Individual intelligence is not only seen from intellectual intelligence but also from emotional intelligence and spiritual intelligence. Spiritual intelligence is the intelligence of the soul. Spiritual intelligence is what can help heal and build ourselves as a whole. The aspects contained in Q.S Luqman verses 12-19 include aspects of faith, aspects of willingness to sacrifice for others, aspects of love and affection and aspects of ethical and polite willingness. The implications of spiritual intelligence for Islamic education methods are that if aspects of spiritual intelligence are inserted into Islamic education methods, it will have a positive impact on students. Because spiritual intelligence basically comes from within the heart which makes a person creative in dealing with personal problems and trying to interpret what is contained therein, and can solve them with a calm heart and mind. This article attempts to explain the aspects of spiritual intelligence contained in Q.S Luqman verses 12-19 and their implications for Islamic education methods using the literature study method, namely reviewing and examining various books, articles, and readings that are relevant to the main theme of this journal.